If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -3(x + 4) = 9 Reorder the terms: 15 + -3(4 + x) = 9 15 + (4 * -3 + x * -3) = 9 15 + (-12 + -3x) = 9 Combine like terms: 15 + -12 = 3 3 + -3x = 9 Solving 3 + -3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -3x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = 9 + -3 -3x = 9 + -3 Combine like terms: 9 + -3 = 6 -3x = 6 Divide each side by '-3'. x = -2 Simplifying x = -2
| x/2+4=x/4-1 | | -4+7y=-9y+4 | | 6(3x-2)=2+4x | | x/3+5=x/6-6 | | 5x+6-3x=3x-2 | | Ln(3x^2+5x)=ln(6x+10) | | e=.046+[e(.091)-.046]1.46 | | 2x^3-x^2-X=5 | | -X+2=X-3 | | Ln(2x)=6 | | y(2y+y-3y+6)= | | 50=w+28 | | -3x^2+12+16x=0 | | 13+a=26 | | graph-4x+2y=8 | | c+93=171 | | 3(6x-1)/2(x-1) | | 5(-1/5)+1=0 | | 72=h+48 | | 44=42+k | | 50+x+3=180 | | -3/6-5/7 | | (x/60)+(y/40)=1.2 | | -3/5-5/7 | | w/4+2=22 | | 62=g+25 | | 56+3x-x^2=2x | | 30-x^2=-x | | -4-7y=9y+4 | | 2.69x+21.52=43.04 | | x+-4y=7 | | 6x-77=3x-8 |